"Ca o vej’eu assaz om’ordinhado". Airas Nunes in the Troubadour Clerical “Choir” - Souto Cabo, José António (Madrygal. Revista de Estudios Gallegos, 2023)
The main aim of this paper is to update data concerning the poets that make up the so-called “compilation of clerics” included in manuscript tradition of Galician-Portuguese lyrical poetry. This group is composed of the poets Airas Nunes, Gomes Garcia, Martim Moxa, Paio de Cana, Rui Fernandes de Santiago and Sancho Sanches, to which we can add A. Gomes, a minstrel from Sárria, also included in the compilation because he dedicated a satirical song to Martim Moxa. In the general review of the historical news that has to do with them, some with a poetic reflection, those about Rui Fernandes and Airas Nunes are highlighted. In the former case, it was possible to obtain unpublished information regarding his professional path, and above all, his family integration. As for the latter, the most important aspect referring to Airas Nunes is the proposal of his historical identification with the homonymous priest recorded, between 1250 and 1292, in the documentation available at the Cathedral of Lugo. In fact, there was no reliable evidence of the life course of one of the most outstanding and original personalities of troubadour lyricism, in addition to the fact that he was the only poet whose involvement in the Cantigas de Santa Maria seems undeniable. With the data that we now have, it is possible to confirm the definition of the group in question as one formed by clergymen of Galician origin associated with a cathedral chapter during the last third of the 13th century.